Digital Holography, a metrological tool for quantitative analysis: Trends and future applications. (May 2018) - Paturzo, Melania; Pagliarulo, Vito; Bianco, Vittorio; Memmolo, Pasquale; Miccio, Lisa; Merola, Francesco; Ferraro, Pietro
Highlights: We review on recent applications of digital holography in different fields of science and technology. We show how digital holography is a powerful metrological tool for a non-invasive inspection of diverse materials. We focus on the advantages of digital holography as a label-free quantitative analysis tool in life sciences. Abstract: A review on the last achievements of Digital Holography is reported in this paper, showing that this powerful method can be a key metrological tool for the quantitative analysis and non-invasive inspection of a variety of materials, devices and processes. Nowadays, its range of applications has been greatly extended, including the study of live biological matter and biomedical applications. This paper overviews the main progresses and future perspectives of digital holography, showing new optical configurations and investigating the numerical issues to be tackled for the processing and display of quantitative data.